ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG PASAR KOTA KABUPATEN WONOGIRI - Wanda Putri, Monica; Safar Nasir, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The economic development of a country cannot be separated from the economic activities of the community. The market has a very important role in the economic activities and development of a country. With the existence of markets, it is very helpful for consumers, producers and governments to generate income. This study aims to analyze the factors that influence the income of Wonogiri Regency City Market traders. This study uses quantitative research and multiple linear regression models. Data sources come from observations, interviews and questionnaires. The number of samples in this study were 95 respondents. With data processing techniques using classical assumption tests and hypothesis tests, and analyzing data using multiple linear regression using Eviews 12 software. The results of this study indicate that business capital, business location, length of business and working hours have a positive effect on the income of Wonogiri Regency City Market traders.